Dinamika Pertumbuhan Mazhab Fiqih: Analisis Historis, Faktor Perkembangan, dan Relevansinya dalam Kajian Fiqih Perbandingan - Siti Patimah; Nur Aini; Dika Merlianda; Gilang Irhamsyah; Saifuddin Yuliar (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The history of the growth and development of schools of thought is an important part of comparative fiqh studies because it describes the dynamics of Islamic legal thought from the time of the companions to the period of codification of schools of thought. This study is motivated by the importance of understanding the historical process of the birth of schools of fiqh as an effort to place differences of opinion in a proportional and scientific manner. This study aims to analyze the growth and development of schools of thought in Islamic law and the factors that influence them. The method used is library research by examining various classical and contemporary literature relevant to the study theme. The results of the study show that major schools of thought such as Hanafi, Maliki, Shafi'i, and Hanbali developed through a process of ijtihad influenced by social, cultural, political conditions, and differences in the methodology of istinbāṭ law. This development does not indicate division, but rather enriches the treasury of Islamic law and provides flexibility in responding to the issues of the ummah in various contexts. The implication of this study is the importance of historical understanding in comparative fiqh studies in order to build a tolerant attitude towards ikhtilaf and strengthen the relevance of Islamic law in facing the dynamics of modern society.